PELAKSANAAN SUPERVISI PEMBELAJARAN SEBAGAI UPAYA MENINGKATKAN TUGAS DAN PERAN GURU DALAM MENGAJAR - Ubabuddin Ubabuddin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
One of the ways in which the teacher profession is developed is by conducting supervision. Supervision is all the efforts of school officials in leading teachers and other education personnel, to improve teaching, including stimulating, selecting the growth and development of teacher positions, selecting and revising educational goals, teaching materials, and teaching methods and teaching evaluation . Supervision in schools is carried out by the principal who acts as a supervisor, so he must be able to carry out a variety of supervision and control to improve teacher performance. The supervisor's role is to provide guidance, direction, and guidance for the teacher's teaching and learning process for improvement. These improvement steps are intended to make the teaching and learning process and the roles and tasks of the teacher more professional.